Synthesis of 8-[2-(amino-oxy) Ethylamino]-6-Methoxy Quinoline Hydrohalide and Related Compounds as Potential Antimalarials - Talesara, G.L.; K.S. Suresh, (Late) (Asian Journal of Chemistry, 2010)
Some of 8-Aminoquinolines containing amino-oxy group have been prepared for the first time by hydrolysis of their precursor phthalimidoxy compounds and both the series screened for cardiovascular activity.